2013
DOI: 10.3109/03014460.2013.856938
|View full text |Cite
|
Sign up to set email alerts
|

Trends in thin body stature among Japanese male adolescents, 2003–2012

Abstract: Thin body stature was documented in increasing proportion of Japanese male adolescents. BMI z-scores decreased across the entire BMI centile spectrums, indicating that the whole school population may be at risk of thinness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The BMI cut-off points were based on averaged data from six different countries, including Asian countries; these cut-off points have been shown to be applicable to Japanese children [ 19 ]. The BMI cut-off points have been used in numerous studies in Japan [ 3 , 4 , 10 , 19 , 20 ]. In the present study, the BMI cut-off points for childhood underweight, overweight, and obesity were 14.35, 19.10, and 22.77 (age 9), and 14.64, 19.84, and 24.00 (age 10), 15.35, 21.22, and 26.02 (age 12) and 15.84, 21.91, and 26.84 (age 13) for boys, and 14.28, 19.07, and 22.81 (age 9), and 14.61, 19.86, and 24.11 (age 10), 15.62, 21.68, and 26.67 (age 12) and 16.26, 22.58, and 27.76 (age 13) for girls, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMI cut-off points were based on averaged data from six different countries, including Asian countries; these cut-off points have been shown to be applicable to Japanese children [ 19 ]. The BMI cut-off points have been used in numerous studies in Japan [ 3 , 4 , 10 , 19 , 20 ]. In the present study, the BMI cut-off points for childhood underweight, overweight, and obesity were 14.35, 19.10, and 22.77 (age 9), and 14.64, 19.84, and 24.00 (age 10), 15.35, 21.22, and 26.02 (age 12) and 15.84, 21.91, and 26.84 (age 13) for boys, and 14.28, 19.07, and 22.81 (age 9), and 14.61, 19.86, and 24.11 (age 10), 15.62, 21.68, and 26.67 (age 12) and 16.26, 22.58, and 27.76 (age 13) for girls, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, the prevalence of obese boys and girls increased from 6.1 and 7.1 %, respectively, in the time-period 1976 to 1980, to 11.1 and 10.2 % in 1996 to 2000 [ 2 ]. Moreover, recent studies have reported that the prevalence of thinness among Japanese adolescents boys and girls have progressively increased from 2.8–4.7 and 2.0–5.7 % in 2003–2004, respectively, to 5.1–7.6 and 3.5–7.8 % in 2011–2012 [ 3 , 4 ]. Thinness, overweight and obesity among children and adolescents can lead to adverse health effects [ 5 , 6 ], and should therefore be considered serious public health problems.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that underweight adolescents are likely to be underweight in young adulthood. Therefore, it is important to prevent underweight in adolescents for their health during both adolescence and adulthood, particularly in Japan, where the prevalence of underweight has increased among adolescents during recent years [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Matsushita et al showed increasing trends in obesity prevalence in school children [2]. However, Inokuchi et al reported that the prevalence of thinness among Japanese adolescents has progressively increased [3,4]. Because thinness, overweight and obesity in adolescence have several adverse effects on health [5,6], these are serious public health issues.…”
Section: Introductionmentioning
confidence: 99%